George Washington and the origins of the American presidency - Rozell, Mark J.; Pederson, William D., 1946-; Williams, Frank J. (Praeger, 2000)
This collection of essays is a retrospective analysis of the Washington administration's importance to the understanding of the modern presidency. The text also looks at different aspects of presidential powers, and at Washington's varying press coverage.